Education Program Evaluation P5 (Pancasila Student Profile Strengthening Project) Using CIPP - Heni Prasetyowati; Ade Iriani; Bambang Ismanto (CV. Publikasi Indonesia, 2024)
This study aims to evaluate the implementation program of the project to strengthen the Pancasila student profile (P5) in the independent curriculum at SDN Genting 02, Jambu District, Semarang Regency, which is a driving school. The research method used is a type of evaluation research using a qualitative descriptive method. This research uses the CIPP evaluation model (context, input, process, product). Data collection techniques used interviews, documentation studies, and observation. Data analysis techniques include Data collection, data reduction, data presentation, and drawing conclusions, in accordance with data analysis techniques according to Miles and Huberman. The research findings indicate that the P5 context aspect is crucial for boosting student achievement and fostering enthusiasm for learning. The Input aspect, namely in the fields of planning, schedules, implementation mechanisms, teachers, staff, financing, facilities, and infrastructure are appropriate but there is a need for improvement in several fields. The results of research on process aspects include preparation, activity process, obstacles, and aspects of suitability to the needs of students. The results of research on the product aspect are the increasing academic and non-academic achievements of students, and also good character in students.